The Dysmorphic Concern Questionnaire in the German General Population: Psychometric Properties and Normative Data - Schieber, Katharina; Kollei, Ines; Zwaan, Martina De; Martin, Alexandra (Aesthetic Plastic Surgery, 2018)
BACKGROUND: The Dysmorphic Concern Questionnaire (DCQ) is a widely used screening instrument assessing dysmorphic concerns ranging from a mild to an excessive level. It is often used in the setting of plastic and aesthetic surgery. The present study aimed at examining the psychometric properties of the DCQ in a random general population sample. METHODS: A representative sample of the German general population (N = 2053, aged between 18 and 65 years, 54% females) completed the DCQ as well as questionnaires on depression and appearance concerns. RESULTS: The DCQ showed a good internal consistency with Cronbach's α = 0.81. Its one-factor model structure was confirmed. Normative data were stratified according to gender and age. Women reported more dysmorphic concerns than men, but also within females the DCQ scores differed between age classes. Overall, 4.0% of the sample reported excessive dysmorphic concerns based on a previously defined cutoff sum score ≥ 11. CONCLUSION: The DCQ is a valid and reliable screening tool to identify individuals with excessive dysmorphic concerns. Excessive concerns may indicate also the presence of body dysmorphic disorder, but for verifying a final diagnosis the use of a structured clinical interview is necessary. LEVEL OF EVIDENCE IV: This journal requires that authors assign a level of evidence to each article. For a full description of these evidence-based medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
EVALuna2:214444